Potential Development of Hydrogen Production from Biomass in Malaysia: A Brief Perspective - Ahmad, Murni M (World Academy of Research and Publication, 2011)
The future form of energy might be hydrogen which is a highly attractive clean energy carrier especially when mentioned as an everlasting energy source. Another advantage would be having water as a by-product from hydrogen combustion to get the energy thus reducing the pressing greenhouse issues raised from fossil fuel usage. The insecurity in fossil energy prices and sources further heightens the demand for an alternative, sustainable and clean energy carrier. Furthermore, currently Malaysia produces substantial amount of biomass in the form of agricultural wastes. Rather than the current practice of disposing these biowaste via open burning that can aggravate the environmental issues, these biomass can be converted into hydrogen. However, the general public is still very unfamiliar with the idea of hydrogen as an energy source. This paper discusses the potential of the development of hydrogen production industry in Malaysia from different perspectives: society, government, research, and industry.